Ensino e aprendizagem matemática numa abordagem psicopedagógica - BARBOSA, Edilene Machado (2022)
The present work entitled Teaching and Learning Mathematics in a Psychopedagogical approach presents the difficulties with the discipline of Mathematics expressed by 6th grade students and teachers interviewed. For this, an exploratory qualitative research was carried out, in which the information was elaborated by means of questionnaires applied in the classroom with the class and an interview with the professors which carries out a descriptive and explanatory case study that comes to investigate a phenomenon within the context of reality itself. In addition, a survey of authors who commented on barriers in the Teaching of Mathematics, active methodologies and the association with Psychopedagogy for the enrichment of studies was carried out. Six teachers from the public school system and twenty-seven sixth-grade students participated in the research. Through the results, it was observed that even with the lack of Continuing Education for teachers, it is possible to verify that there is a dedication and a charm when it comes to teaching. Also relevant was the psychological disorders of students who regularly already have a baggage related to Learning, which leads to creating ideas about judgments regarding the subject of Mathematics. In view of this, we came to the conclusion that the ability to learn is individualized and built in the face of Psychopedagogical devices that open the way for more meaningful learning.